Look Out, There is a Triangle behind You! The Effect of Primitive Geometric Shapes on Perceived Facial Dominance. (1st January 2013) - Toet, Alexander; Tak, Susanne
Previous research has shown that perceived facial valence is biased toward background valence. Here, we examine whether background dominance also affects perceived facial dominance. In particular, we hypothesized that downward-pointing triangles, which are known to convey threat, would affect perceived facial dominance. Participants judged perceived facial dominance of neutral faces presented overlaid on downward- or upward-pointing background triangles. Our results show that neutral faces are indeed judged more dominant when seen with a downward-pointing triangle in the background. The fact that simple geometric background shapes can affect facial judgments may have important implications for the design and experience of our daily environment and multimedia content.